Creating A Healthy Lifestyle of Students Through the Use of The SEKA Application (Health Campus) - Aryani , Enggar Wahyu Putri; Ramadhan, Persistent; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
In this modern era, a healthy lifestyle has become a major concern for many people, including students. College students often face high academic pressure and social demands, which can have a negative impact on their health. Therefore, it is important for students to maintain their physical and mental health so that they can optimally achieve their academic and personal potential. A healthy lifestyle is becoming increasingly important in everyday life, especially for students who often face academic pressures and lack a lifestyle. Healthy. To help students maintain their health, we propose to make an application called "SehatKampus". This application will be a guide and support for students to live a healthy lifestyle practically and effectively. The method used to manage student health activities is to use the application. Seka.com is the domain for relevant technology. This study was conducted with a qualitative approach. Qualitative research uses descriptive data from individuals and observable actors to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs, and perceptions. The Healthy Campus Application (SEKA) stands for healthy campus. Seka itself can be interpreted in Javanese as a healer. This seka application is designed to become a student facilitator in maintaining health and stabilizing their healthy lifestyle. This application is equipped with various features which can support a student's healthy lifestyle. In order to assist students in living a healthy lifestyle, developing a special application can be an effective solution. This application can provide easy access and relevant information about health to students. The following are reasons that explain why student healthy living apps are important and the benefits they can provide: Based on research on campus healthy apps, it can be concluded that the use of campus healthy apps has great potential to improve student health and well-being. These apps can provide useful information, facilitate access to health services, and provide features that promote a healthy lifestyle. In this study, it was found that college students tended to respond positively to using campus healthy apps and reported benefits in increasing health awareness and helping them manage a healthy lifestyle.